Pelatihan Guru SD Gugus Suntalangu dalam Pemanfaatan IT dan AI untuk Optimalisasi Pembelajaran Literasi Berdiferensiasi - Novitasari, Dwi; Sripatmi, Sripatmi; Prayitno, Sudi; Amrullah, Amrullah; Junaidi, Junaidi; Zikrullah, M. Riki (Rengganis Jurnal Pengabdian Masyarakat, 2025)
Elementary students’ literacy skills in East Lombok remain relatively low, while the use of digital devices in schools is still limited. This community service aimed to enhance the competence of elementary teachers in Gugus Suntalangu in utilizing information technology (IT) and artificial intelligence (AI), particularly Diffit, to support differentiated literacy learning. The program applied a participatory approach through training, hands-on practice (learning by doing), classroom implementation, mentoring, and reflection. Instruments included questionnaires, classroom observations, focus group discussions (FGD), and assessment of teachers’ learning products. A total of 34 teachers actively participated. Questionnaire results indicated that all teachers responded positively, affirming that IT- and AI-based media are curriculum-relevant, easy to use, engaging, and feasible to implement. The outputs included training modules, AI-based literacy assessments using Diffit, and digital media products such as AR, VR, and local culture-based digital storytelling. This program demonstrates that integrating IT and AI can strengthen teachers’ skills and has strong potential for replication in other school clusters.